Contemporary Innovation in China. Issue 5 (3rd September 2019) - Lo, Y. Ling; Li, Yanqiong; Chan, Kam C.
Abstract : We discuss the development of contemporary innovations in China and how these innovations influence its economic success. Specifically, we present contemporary innovations of mobile payments, shared bicycles, WeChat, high-speed rail, and human-less hotels; we discuss how these innovations enhance the welfare of consumers, performance of firms, and economic growth. These innovations have helped to promote the Chinese economy by increasing its efficiency and reducing transaction costs. Thus, the fast economic growth in China is accompanied with improved quality of life among Chinese people.